SIPUKET (SISTEM INFORMASI PELAYANAN UMUM PEMBUATAN SURAT KETERANGAN) BERBASIS WEB PADA KELURAHAN TEGALMUNJUL - Suryani, Nining; Hidayat, Tino; Priyanti, Evy; Sihombing, Girman (JURNAL AKADEMIKA, 2024)
People in the Tegalmunjul sub-district are forced to travel home to retrieve personal files or documents that do not meet the requirements for making a certificate because the system is still operated manually. Examples of these documents include incomplete KTP, KK, or other personal documents that are required for making a certificate. People typically have to wait a very long period to receive a certificate. Time is lost waiting for the letter to be written, making this less efficient and effective. For all system requirements to be satisfied, a system or software must be in place that allows individuals to simply pick up the completed letter, initials, and stamp subdistrict. In this study, correspondence software is developed using the prototype technique in the hopes of improving the effectiveness of correspondence activities for the community.